An evaluation of autothermal thermophilic aerobic digestion (ATAD) of municipal sludge in Ireland. Issue 1 (1st January 2007) - Layden, Noreen M
Abstract : Autothermal thermophilic aerobic digestion (ATAD) is an exothermic process where sludge is subjected to temperatures greater than 55 °C and a hydraulic retention time of 6–15 days. Organic solids are degraded and the heat released during the microbial degradation maintains thermophilic temperatures. Autothermal thermophilic aerobic digestion can produce a biologically stable product while reducing both sludge mass and volume. The full-scale ATAD facility in Killarney, Ireland, is unique because the feed sludge is blended from three different secondary treatments and there are seasonal fluctuations in hydraulic load. An assessment of the on-site operational and solids data showed that the process operation has improved since commissioning. Total solids reduction increased from 13.7% in 2001 to 39.1% in 2004. Also, despite some operational problems the regulatory target of 38% reduction in volatile solids was achieved. The data fluctuated but the percent reduction in volatile solids increased from 35.6% in 2001 to 49.8% in 2004. This paper compares the process data obtained from the Killarney site with other ATAD facilities operated in Europe and North America. It discusses some of the operational changes employed to deal with process control issues and it presents recommendations for enhanced ATAD process improvement. Key words : autothermal, thermophilic, aerobic, digestion, sludge, biosolids.